Human development - Freiberg, Karen ed. (McGraw-Hill/Dushkin, 2003)
Contents: Genetic and prenatal influences on development,development during infancy and early childhood,development during childhood : cognition and schooling,development during childhood : family and culture,development during adolescence and young adlthood,development during middle and late adulthood.
Incluye bibliografía Includes bibliographical references and index
Keywords: Human Development - Periodicals